ANALYSIS DETERMINANTS OF INDONESIAN PALM OIL EXPORT VOLUME TO TEN MAJOR DESTINATION COUNTRIES - Widad, Zahratul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
This research is entitled Analysis of Determinants of Indonesian Palm Oil Export Volume to Ten Major Destination Countries. Economic growth also varies among these countries. India's economy grew steadily with an average annual growth rate of 5.2%, which is likely to increase its demand for palm oil. China's economy, despite a slight decline in 2020 due to COVID-19, rebounded with an average annual growth of 3.9%. This study aims to analyze the determinants of Indonesia's palm oil export volume to ten major destination countries during the period 2012-2022 using a descriptive quantitative approach with panel data that combines time series data and cross-sectional data. Secondary data was obtained from various sources such as BPS, Investing.com, World Bank, and Macrotrends. The analysis method used includes panel data regression with the selection of the best model through Chow and Hausman tests, as well as classical assumption tests and goodness of fit tests. The results show that the international price of palm oil has a positive effect on export volume, while the exchange rate, economic growth of importing countries, and inflation in Indonesia have a negative effect. Overall, these economic variables have a significant effect on Indonesia's palm oil export performance. This study model indicates that the independent variables (international prices, exchange rate, economic growth, and inflation) collectively explain 94.10% of the variation in Indonesian palm oil export volume. This indicates that these economic factors exert a strong influence on the performance of Indonesian palm oil exports.